STRATEGI PENGEMBANGAN KUALITAS KARYAWAN (STUDI PADA PT BANK CENTRAL ASIA KCP SUMENEP) - Fara Aryanti Risma Ayu; Satunggale Kurniawan; Muhammad Afifi Rahman (PT. Jurnal Center Indonesia Publisher, 2024)
The objective of this research is to know the applied strategy of employees quality development, the programs applied and the obstacles which are experienced by PT Bank Central Asia – KCP Sumenep in developing their employees. The researcher used the employees’ development theory by Werther & Davis as the approach of analysis. Besides, the researcher also used the employees’ development theory by Hasibuan. This research is descriptive describing and analyzing collected data during the research with qualitative approach. The researcher made Mrs. Nurmalia Puspitarini as interviewee and main informant from BCA side; she is the Head of Service BCA Sumenep. The interviewee was chosen because she knows directly the strategy of employees quality development which is done by BCA. The result shows that the strategy of employees’ quality development of BCA Sumenep is done through training and education method. Training and education programs were done by on the job training, pre-service education and coaching, and also off the job training, regular training, e-learning, smartsolution reward program, video-based training, worklife balance, community of practice, and service dialogue. Coaching program, e-learning and regular training succeed to increase the employees’ quality and work rate. The obstacles which are experienced by BCA are tight working hours and limited development funds, conditional difference in region and the absence of human resource division in branch office